Factors affecting economic growth in Malaysia / Nurizzati Syazwani Noradzmi - Noradzmi, Nurizzati Syazwani (Faculty of Business and Management, 2017)
Economic growth (GDP) plays an important roles to ensure a better position of economic and positive image of a country. Malaysia's economic growth in term of GDP (current US$) were declining in 1998, 2009, and 2015. The aim of this study is to examine the relationship between export, unemployment, population, inflation, and foreign direct investment (FDI) on economic growth of Malaysia by using the time series data the year of 1985 to 2015. This study used secondary data to be run in the E-views software while the models that being used is Multiple Linear Regression to find the relationship between all independent variables and dependent variable. Based on the empirical result by unit root test, export has a positive and significant effect while inflation has positive but insignificant effect on economic growth. Meanwhile unemployment and population shows significant but has a negative relationship with GDP. Lastly, FDI shows that it has negative and insignificant effect with GDP. Therefore, this study might be useful for policy makers, investors and public.